Rozłóż czynniki wyłączając wspólny czynnik poza nawias ;
A) ac+bc+a+b
B) x²-xy-2x+2y
C)x²+xy+ax+ay
D)x³+3x²+3x+9
E)x²-xy-2x+2y
F)m²+mn-5m-5n
G)a²-ab-3a+3b
H)10ay-5by-2ax-bx
I )6by-15bx-4ay+10ax
J)5a²-5ax-7a+7x
K)ax²+bx²-bx-ax+a+b
L)ax²+bx²+ax-cx²+bx-cx
M)ax²+bx²-bx-ax+cx²-cx
N)5ax²-10ax-bx+2b-x+2



1

Odpowiedzi

2010-03-08T18:05:16+01:00
A) ac+bc+a+b= (ac+a)+(bc+b)= a(c+1)+b(c+1)=(c+1)(a+b)
b) x²-xy-2x+2y=(x²-2x)-(xy+2y)=x(x-2)-y(x-2)=(x-2)(x-y
C) x²+xy+ax+ay= (x²+xy)+(ax+ay)=x(x+y)+a(x+y)=(x+y)(x+a)
D) x³+3x²+3x+9=(x³+3x²)+(3x+9)=x²(x+3)+3(x+3)=(x+3)(x²+3)
E) x²-xy-2x+2y=(x²-xy)-(2x+2y)=x(x-y)-2(x-y)=(x-y)(x-2)
F) m²+mn-5m-5n=(m²-5m)+(mn-5n)=m(m-5)+n(m-5)=(m-5)(m+n)
G) a²-ab-3a+3b=(a²-3a)-(ab+3b)=a(a-3)-b(a-3)=(a-3)(a-b)
H) 10ay-5by-2ax-bx=(10ay-5by)-(2ax-bx)=5y(2a-b)-x(2a-b)=(2a-b)(5y-x)
I ) 6by-15bx-4ay+10ax=(6by-4ay)-(15bx+10ax)=2y(3b-2a)-5x(3b-2a)=(3b-2a)(2y-5x)
J) 5a²-5ax-7a+7x=(5a²-7a)-(5ax+7x)=a(5a-7)-x(5a-7)=(5a-7)(a-x)
a reszte to może ktoś inny zrobi bo nie wiem jak :P pozdrawiam :)